The turncoat's gambit - Cremer, Andrea R. (Cremer, Andrea R. Inventor's secret, 2016)
"In an alternate nineteenth-century America, Charlotte is on the run from both the empire and the revolution. Now she must figure out whom she trusts, once and for all"--